OP0264 Glucosepane : a new biomarker of the severity of osteoarthritis. (12th June 2018) - Rabbani, N.; Ahmed, U.; Lambert, C.; Legrand, C.; Anwar, A.; Rajpoot, K.; Pasha, S.; Davidson, R.K.; Clark, I.M.; Thornalley, P.J.; Henrotin, Y.
Abstract : Background: Glycation, oxidation and nitration of proteins are reactions involved in accelerated ageing of tissues. The products of these reactions are used as biomarkers of chronic pathologies such as diabetes or chronic inflammatory states. Objectives: In this work, we studied by mass spectrometry the levels of amino acids and glycated, oxidised or nitrated proteins in culture media of chondrocytes cultivated in multi-layers and in the blood of guinea pigs or osteoarthritis patients. Methods: Sixty male, 3-week-old Dunkin-Hartley guinea pigs were used in this work. At 4-weeks-old and 8 week intervals until week 36, twelve animals were sacrificed and histological severity of knee osteoarthritis evaluated and cartilage rheological properties. Human patients with early and advanced osteoarthritis and healthy subjects were recruited. Human chondrocytes cultured in multilayers were treated for 10 days with interleukin (IL) −1β. Amino acids and glycated, oxidised and nitrated proteins were analysed in the serum of guinea pigs, osteoarthritis patients and in the culture medium conditioned by chondrocytes by stable isotopic dilution analysis liquid chromatography-tandem mass spectrometry using the Acquity UPLC system. Results: Severity of osteoarthritis increased progressively in guinea pigs with age. Glycated, oxidised and nitrated amino acids were increased markedly at week 36. Glucosepane and dityrosine increased progressively from weeks 20 and 28, respectively. Glucosepane was positively correlated with the OA histological severity (r=0.58, p<0.0001) and the Young's modulus (r=0.52–0.56, p<0.0001). Oxidation free adducts were positively correlated with OA severity (p<0.0009–0.0029) and hydroxyproline with cartilage thickness (p<0.0003–0.003). In the clinical study, plasma glucosepane was increased 38% in patients with early osteoarthritis (p<0.05) and 6-fold in patients with advanced osteoarthritis (p<0.001) compared to healthy subjects. IL-1β increased the release of glycated, oxidised and nitrated products from chondrocytes in vitro . Conclusions: The glycation, oxidation and nitration of proteins are reactions related to the severity of osteoarthritis. The products of these reactions are measurable in blood by mass spectrometry and could be biomarkers of osteoarthritis. More specifically, glucosepane is an advanced glycation product very strongly increased in the severe form of the disease. In conclusion, serum glucosepane is a potential biomarker for diagnosis and progression of osteoarthritis. Disclosure of Interest: None declared